Microbiome analysis reveals gut bacterial alterations in adult Tibetan pigs with diarrhea - Wu, Zhoulin; Li, Xiaoyu; Wang, Yan; Zhang, Jiamin; Ji, Lili; Gan, Ling (Frontiers in Microbiology, 2025)
Diarrhea is a significant ailment that causes heavy economic losses in the pig industry. The Tibetan pig is a native Chinese breed that is unique to high-altitude regions and displays strong disease resistance. However, scientific research on the structural characteristics of the gut microbiota and key genera associated with diarrhea in Tibetan pigs is still scarce, especially those involving adult Tibetan pigs. In this study, fresh fecal samples from diarrheic (case, N = 9) and healthy adult Tibetan pigs (control, N = 10) were collected and sequenced using 16S rRNA gene sequencing. Our results revealed that the gut microbial community of the case pigs exhibited lower alpha diversities but higher intragroup variability in microbiota composition. The genera Treponema and Prevotellaceae_UCG-001 were underrepresented in the pigs, serving as hallmarks of diarrhea, while Lactobacillus, Escherichia-Shigella, and Muribaculaceae showed increased abundance. Moreover, the genera Lactobacillus and Ignatzschineria were significantly enriched biomarkers in the case pigs. Notably, these changes were not consistent with those observed in Tibetan piglets and other commercial pigs. Furthermore, the decreased abundance of Treponema in the diarrheic pigs indicated that this disease was associated with a high-fiber diet and environmental adaptability. The differentially enriched pathways in the case and control pigs further revealed that gut dysbiosis exacerbated immune and inflammatory responses to promote the development of diarrhea. In conclusion, this study characterized the distribution of gut microbiota composition in adult Tibetan pigs with different health status, which may enhance our understanding of the role of the gut microbiota in intestinal issues.